Prevalence and incidence of external genital warts in a sample of Italian general female population. Issue 1 (December 2017) - Suligoi, Barbara; Vittori, Giorgio; Salfa, Maria; Timelli, Laura; Corsini, Dario; Fattorini, Giovanni; Mariani, Luciano
Abstract Background The Human papillomavirus is the most common sexually transmitted virus worldwide. The objective of this study was to estimate: 1) the prevalence and the incidence of external genital warts (eGW) in a sample of women attending community outpatient clinics and 2) the total number of eGW cases in the Italian female population aged 15–64 years. Methods A prospective study was performed for a 12-month period between 2009 and 2010, among a sample of women attending community gynecological outpatient clinics located throughout Italy. Demographic data, for every woman aged 15–64 years, were collected. For women diagnosed with eGW, behavioral and clinical data were recorded. Prevalence of eGW was calculated as the proportion between the number of women with eGW and that of women visiting any of the participating gynecologists; incidence of eGW was calculated as the proportion between the number of women with a new diagnosis of eGW and that of women visiting any of the participating gynecologists. Standardized prevalence by age was used to estimate the number of eGW cases occurring in the Italian female population aged 15–64 years. Results In 2009–2010, 44 community gynecologists were included in the network. In one-year period, 16, 410 women visited any of the participating gynecologists; 63 women were diagnosed with eGW, corresponding to a prevalence of 3.8 cases per 1, 000 women per year (95%CI: 2.9-4.9). The incidence of eGW was 3.0 cases per 1, 000 women per year (95%CI: 2.2-3.9). Women aged 15–24 years showed both the highest prevalence and incidence. Prevalence and incidence significantly decreased by increasing age group (p <0.001), and were higher in Southern Italy compared to Central-Northern Italy. The estimated number of women with eGW among women aged 15–64 years in Italy, in 2010, was approximately 69, 000. Conclusions These data show a high prevalence and incidence of eGW among young women in Italy, stress the effectiveness of community clinical networks in investigating STI epidemiology among women from the general population, confirm the relevance of HPV vaccination programs among adolescents, and underscore the need of promoting safe sex, implementing early diagnosis, treatment and prevention of genital warts.